Humic acids trigger the weak acids stress response in maize seedlings - Daiane Carvalho Baía; Fábio L. Olivares; Daniel B. Zandonadi; Cleiton de Paula Soares; Riccardo Spaccini; Luciano P. Canellas (Chemical and Biological Technologies in Agriculture, 2020)
Abstract Background Plants primed by humic acids showed physiological and molecular response against different abiotic stresses without the presence of stressor agents (salinity, drought, heavy metal toxicity). It is plausible that humic acids themselves can act as chemical priming substances in plants. We hypothesized that humic acids can trigger the weak acids stress response in cell plants acidifying the cytosol and thus eliciting the transduction signalling response cascade. Methods The dose–response curves of maize seedlings roots with different concentrations of humic, acetic and salicylic acids determined the most active and inhibitory concentration. These data were further used to evaluate changes on intracellular pH using BCECF-AM probe (2,7-bis(2-carboxyethyl)-5(and 6)-carboxyfluorescein, acetoxymethyl ester) and differential transcription level of genes related to weak stress response in plants by qPCR real time. Results Humic acids like short chain organic acids decrease the intracellular pH showed by the increased fluorescence of BCECF probe. The drop in cytosolic pH promoted by humic acids was not transient. We observed a high level of protein kinases related to cell energy-sensing and transcription factors associated to transduction of stress signalling. Conclusion The humic acids can be considered as a chemical priming agent, since in the appropriate concentration they can induce the typical plant abiotic stress response of weak acids inducing plant acclimation and enhancing the abiotic stress tolerance.